The Influence of Student Motivation on Career Interests in the Field of Taxation - Tiara Aninda Rahma Dhamara Putri (Journal of Contemporary Information Technology, Management, and Accounting, 2022)
The need for a motivation to encourage students majoring in career accounting, especially in the field of taxation, is discussed in this research. The research aims to find out the influence of career motivation, economic motivation, and social motivation on students' interest in a career in taxation. Quantitative research method with research type used is explanatory research. This study examined the relationship between student perception and motivation with a career interest in taxation. The population of this research data is a student majoring in accounting faculty of economics and business class of 2017 at the State University of Malang. The results of this study based on the hypothesis is H1: Student career motivation has a positive influence on career interests in the field of taxation there is a significant influence. H2 : Student economic motivation has a positive effect on career interests in the field of taxation does not have a significant impact. H3 : Student social motivation has a positive effect on career interests in the field of taxation has no significant effect.